Halal Purchase Intention on Processed Food - Saniatun Nurhasanah; Happy Febrina Hariyani (Tazkia Islamic Finance and Business Review, 2017)
The objective of this study is to investigate the factors affecting customers on purchasing halal purchase intention on processed food. A purposive sampling method with 193 respondents and the data analysis is done by SEM-PLS method. The results show that halal awareness, health reason, and perceived value have a significant and positive direct effect on purchasing intention. Halal marketing also shows a significant and positive effect on purchasing intention. The food safety, halal certification, brand image, and perceived quality show the same effect which has no direct effect on purchasing intention. Furthermore, Food safety has an indirect effect on purchasing intention through health reason. Halal certification has an indirect effect on purchase intention through brand image variable. Meanwhile, brand image and perceived quality have an indirect effect through perceived value variable on purchasing intention.